1985
DOI: 10.1017/s0022172400062215
|View full text |Cite
|
Sign up to set email alerts
|

Biotypes and serotypes of thermophilic campylobacters isolated from cattle, sheep and pig offal and other red meats

Abstract: SUMMARYIn this study we examined 730 faecal samples of offal (mainly liver), mince-meat and sausage meat collected from abattoirs and retail butchers' shops for campylobacters.Campylobacter jejuniorC. coliwere isolated from 30·6, 10·5 and 6% of sheep, cattle and pig offal samples respectively. Specimens collected from abattoirs were, in general, more often contaminated than material obtained from retail butchers' shops. Only 1·4% of minced meats and sausage meats contained campylobacters. Most isolates (89·5%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Gross microbial contamination of the carcass with gut contents may occur during evisceration but it is thought that most contamination occurs during removal of the hide or from cross‐contamination from hide to carcass via hands and instruments of slaughtermen (Gannon 1999). Although rates on offal tend to be higher (Bolton et al 1985), most, if not all, surveys over the last two decades have found that the incidence of Campylobacter on red meat is low compared with poultry meat even when other pathogens, such as Salmonella and Escherichia coli O157, can be isolated. An extensive survey of 1400 butchery products and premises isolated Campylobacter spp.…”
Section: 2 the Significance Of Ruminant Sources Of Infectionmentioning
confidence: 99%
“…Gross microbial contamination of the carcass with gut contents may occur during evisceration but it is thought that most contamination occurs during removal of the hide or from cross‐contamination from hide to carcass via hands and instruments of slaughtermen (Gannon 1999). Although rates on offal tend to be higher (Bolton et al 1985), most, if not all, surveys over the last two decades have found that the incidence of Campylobacter on red meat is low compared with poultry meat even when other pathogens, such as Salmonella and Escherichia coli O157, can be isolated. An extensive survey of 1400 butchery products and premises isolated Campylobacter spp.…”
Section: 2 the Significance Of Ruminant Sources Of Infectionmentioning
confidence: 99%
“…Butzler-type medium (made up of blood agar base, 5% lysed defibrinated horse blood and bacitracin 12,500 IU, cycloheximide 25 mg, colistin sulphate 5,000 IU, cephazolin sodium 7.5 mg, novobiocin 2.5 mg) and Bolton medium (which contains the following antibiotics: vancomycin 20 mg, cefoperazone 20 mg and cycloheximide 50 mg in 1000 ml preparation) were used for the selective isolation of campylobacters. 6,8 Inoculated broth and agar media were incubated at appropriate temperatures (range: 37 o C to 42 o C) and room temperatures. Bolton and Butzler-type media were incubated at 42 o C in 10% CO 2 for 72-96 hours.…”
Section: Bacteriological Analysismentioning
confidence: 99%
“…During making Turkish fermented sucuk and Turkish pastırma, meat is neither cooked nor refrigerated, these products must be safe to consume yet. C. jejuni has been isolated with particular frequency in food products including ground meat and sausage (Baffone et al 1995, Bolton et al 1985. In minced meat, C. jejuni survived better and viable counts were relatively unchanged in minced beef at refrigerator temperatures and 22°C, but showed a decrease in corresponding samples of sausage mixture (Barrell 1984).…”
Section: Discussionmentioning
confidence: 99%